Al-Arbaʿīniyyāt li-Kashf anwār al-qudsiyyāt - Qumī, Qāḍī Saʿīd, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Islamic literature, there is a genre called arbaʿūna ḥadīthan , in which 40 Prophetic traditions are jointly published, mostly with some kind of commentary. The genre finds its origin in the tradition saying that whoever commits forty traditions to memory will be reckoned among the jurists on Resurrection Day. Qāḍī Saʿīd Qumī (d. after 1107/1696) is a Shīʿite philosopher, jurist, physician and mystic of the Safavid period. Having been trained by some of the foremost scholars of his time, he spent most of his active life in Qum, where he divided his time between his judgeship and teaching. In imitation of the forty-traditions genre, Qāḍī Saʿīd wanted to publish a collection of fourty essays, mostly on philosophy and mysticism, as the fruit of his many years of study. In fact, he got no further than ten. Still, this does not detract from their quality, as may be judged from the present edition.